Investigation of the Acoustical Environment of the Elderly’s Living Place - ZENG, Youjie; PENG, Jianxin; ZHAO, Lei (Archives of Acoustics, 2018)
A questionnaire survey was conducted in the residential quarters of Guangzhou, for which 582 elderly people over 60 years old were randomly recruited. The hearing impairment of the participants was evaluated using the Hearing Handicap Inventory for the Elderly (HHIE), The participants’ subjective responses to the acoustical environment of their living place and the impact of the living acoustical environment (LAE) on the participants were investigated. The results show that the participants with a low HHIE score and no hearing impairment evaluated their LAE more favourably, and they considered that the effect of the LAE on their daily life was weak. However, those with a high HHIE score and severe hearing impairment evaluated their LAE poorly, and considered its effect on their daily lives to be significant. For the elderly, the worse the hearing is, the higher their demand for a better LAE. Traffic, construction, residential quarters, and noise from next door or upstairs neighbours were the main noise sources in the elderly’s living places, and traffic noise, construction noise, and noise from next door and upstairs were the most influential sources. 28.9% of the respondents had trouble hearing what their family said in their living place. The elderly without hearing impairment considered that continuous noise was the main reason that they could not hear what their family said in their living place, while those with hearing impairment believed that their own hearing problem was a contributing factor.